2014
DOI: 10.1016/j.jeem.2013.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Saving power to conserve your reputation? The effectiveness of private versus public information

Abstract: a b s t r a c tEnvironmental damage is often an unseen byproduct of other activities. Disclosing environmental impact privately to consumers can reduce the costs and/or increase the moral benefits of conservation behaviors, while publicly disclosing such information can provide an additional motivation for conservation -cultivating a green reputation. In a unique field experiment in the residence halls at the University of California -Los Angeles, we test the efficacy of detailed private and public information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 75 publications
(85 reference statements)
6
98
0
2
Order By: Relevance
“…Please refer to Delmas and Lessem [24] for a full description of the experimental results of the behavioral study. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please refer to Delmas and Lessem [24] for a full description of the experimental results of the behavioral study. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Delmas and Lessem [24] present a thorough analysis and explanation of the results. First, we conducted an exit survey to ask about the efficacy of the dashboard and whether any energy conservation actions were undertaken.…”
Section: Energy Behavior Impactmentioning
confidence: 99%
“…They found that 80% of dashboard activity was generated by 25% of students. Moreover, a behavioral study associated with this experiment [16] compared private to public information effectiveness. Private information was given as a personalized energy dashboard associated with weekly emails, whereas students in the public information group had stickers visibly highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…An influential study within this literature is by [2], which shows how providing utility customers with information on their water use relative to their neighbors leads to energy savings among 4 high consumption users. Coupling such comparative information with normative judgments and making relative performance public increase the effect of comparative information ( [47]; [29]). Laboratory evidence also supports the effectiveness of social norms: contributions to public goods, dictator and ultimatum games are influenced by information on other subjects' individual or average decisions ( [10]; [28]; [38]; [58]; [91]; [25]; [15]).…”
Section: Impact Of Traditional and Behavioral Interventionsmentioning
confidence: 99%